The expression of lncRNA-MALAT1 in breast cancer patients and its influences on prognosis - Sun, Zhenxuan; Liu, Jinquan; Liu, Jintao (Cellular and Molecular Biology, 2020)
This study aimed to explore the expression of lncRNA-metastasis associated lung adenocarcinoma transcript 1 (lncRNA-MALAT1) in breast cancer (BC) patients and its influences on the prognosis of the patients. A total of 120 BC patients admitted to our hospital were enrolled as a BC group, of which 58 patients at I/II stage were treated with breast-conserving surgery as an operation group, and the other 62 patients at III/IV stage were treated with neoadjuvant chemotherapy combined with breast-conserving surgery as a combination group. Meantime, 100 healthy people in physical examination during the same period were enrolled as a normal group. The expression of serum lncRNA-MALAT1 in the subjects was determined, and the expression in BC patients and its influences on the patients were analyzed. LncRNA-MALAT1 was over-expressed in patients from the BC group, and the area-under-the-curve (AUC) of it for diagnosing BC was 0.911. After treatment, the expression of lncRNA-MALAT1 in the operation group and the combination group significantly decreased, and the expression of it in patients with good prognosis was greatly lower than that in patients with poor prognosis. The AUC of lncRNA-MALAT1 for predicting poor prognosis was 0.838, and TNM staging, pathological differentiation, tumor diameter, and lncRNA-MALAT1 were independent prognostic factors for poor prognosis of the patients. Furthermore, low expression of lncRNA-MALAT1 was associated with a relatively high 5-year overall survival (OS) of BC patients. The expression of lncRNA-MALAT1 was up-regulated in BC patients, while it was down-regulated in BC patients treated with breast-conserving surgery combined with neo-adjuvant chemotherapy, so lncRNA-MALAT1 can be used as a potential indicator for early diagnosis and prognosis prediction of BC patients.